Utilization of activated carbon in combination with ionic liquids for removal of halogenated dyes growing parameter AOX from model waste water - Filipi, Michaela; Weidlich, Tomáš (Česká společnost průmyslové chemie, 2019)
This work deals with the removal of chlorinated acid dyes such as Mordant Blue 9 and Acid Yellow 17 from model wastewater using granular activated carbon and ionic liquids. In this work, comparison of granular charcoal adsorption efficiency with subsequent effect of added aqueous mixture of benzylalkyldimethylammonium chloride (benzalkonium chloride) with methyltrialkylammonium chloride (Aliquat 336) on mentioned dyes removal efficiencies was studied. It was observed that addition of ionic liquid to the saturated active carbon enables enhancement of sorption capacity of this adsorbent.
Využití aktivního uhlí v kombinaci s iontovými kapalinami pro odstranění halogenovaných barviv zvyšujících parametr AOX z modelové odpadní vody
Keywords: acid dyes; activated carbon; waste water; kyselá barviva; aktivní uhlí; odpadní voda